Genetic Predisposition to Poor Opioid Response in Preterm Infants: Impact of KCNJ6 and COMT Polymorphisms on Pain Relief After Endotracheal Intubation. Issue 4 (August 2016) - Elens, Laure; Norman, Elisabeth; Matic, Maja; Rane, Anders; Fellman, Vineta; van Schaik, Ron H. N.
Abstract : Background: Single-nucleotide polymorphisms in genes involved in pain control might predispose to exaggerated sensitivity or difference in opioid analgesic effect. The relevance of the KCNJ6 -1250G>A (rs6517442, c.-1787G>A) and the catecholamine- O -methyltransferase ( COMT ) c.472G>A (rs4680, Val 158 Met) single-nucleotide polymorphisms were studied in preterm infants needing intubation and randomized to a premedication strategy including remifentanil (n = 17) or morphine (n = 17). Methods: Pain was scored with Astrid Lindgren and Lund Children's Hospital Pain Assessment Scale every 30 minutes for 6 hours. The pain relief provided by the opioids was compared between the different KCNJ6 and COMT genotypes. Results: Infants homozygous for the KCNJ6 -1250A allele had an increased duration after intubation to achieve a score indicating no pain compared with infants with the A/G or G/G genotypes (182 ± 30, 109 ± 29, and 60 ± 21 minutes, respectively; Logrank = 7.5, P = 0.006). Similarly, the duration was increased in individuals with the COMT Val/Val alleles compared with Val/Met and Met/Met (285 ± 37, 137 ± 25, and 63 ± 15 minutes, respectively; Logrank = 14.4, P = 0.0021). Cox proportional hazards analysis confirmed that the variation in both genes was independently associated with susceptibility to respond to therapy. Conclusion: We conclude that the KCNJ6 -1250A and COMT 158 Val alleles are predisposing preterm newborns to diminished opioid-induced pain relief.